Enhanced thermal stability of the τ-phase in MnAl-C alloys with Ni additions - Feng, Le; Nielsch, Kornelius; Woodcock, Thomas George (Journal of Alloys and Compounds, 2021)
Alloys with compositions (Mn53Al45C2)100−xNix where x = 0, 0.6, 1.5, 2, 4 and 6 were produced, and the microstructure, magnetic properties and thermal stability of the thermodynamically metastable τ-phase, i.e., its resistance to decomposition into the equilibrium phases, were investigated. With x = 0.6 or 1.5, the τ-phase has greater stability than that in ternary alloy (x = 0): after heat treating the homogenised alloys for 7 days at 700 °C, the estimated remaining volume fractions of the τ-phase are 0.35, 0.85 and 0.91 for x = 0, 0.6 and 1.5, respectively. A hot deformed sample of the alloy with x = 0.6 showed less decomposition of τ-phase and smaller recrystallised grain size compared to the alloy with x = 0 in the same state. The solubility limit of Ni in the τ-phase with Mn:Al = 1.18 and approx. 2 at% C addition at 700 °C is below 0.6 at%, however, the solubility of Ni in the ε-phase with the same composition at 1100 °C is in the range 1.5–2 at%.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Magnetic property; MnAl-C; Ni addition; Stability